2015
DOI: 10.1007/s00269-015-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic photoluminescence and EPR features of superdeep diamonds (São-Luis, Brazil)

Abstract: accompanied by the EPR center with g-factor of 2.00285. The 536 and 576 nm vibronic systems totally dominated the PL spectra of superdeep diamonds, while none of "normal" diamonds from the Mir pipe (Yakutia) with similar nitrogen characteristics showed the latter three PL centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…10d, 14a). Additional peaks at 536.8, 537.8, and 505 nm in our samples, as revealed by PL spectroscopy, are absent in lithospheric diamonds globally, but are common in sublithospheric stones (Yuryeva et al, 2015). The defects responsible for these peaks in PL (Collins and Ly, 2002;Tretiakova, 2009) still remain to be resolved.…”
Section: Reasons For the Colors Of Argyle Diamondsmentioning
confidence: 64%
See 1 more Smart Citation
“…10d, 14a). Additional peaks at 536.8, 537.8, and 505 nm in our samples, as revealed by PL spectroscopy, are absent in lithospheric diamonds globally, but are common in sublithospheric stones (Yuryeva et al, 2015). The defects responsible for these peaks in PL (Collins and Ly, 2002;Tretiakova, 2009) still remain to be resolved.…”
Section: Reasons For the Colors Of Argyle Diamondsmentioning
confidence: 64%
“…Other optical defects: Many of the defects responsible for the color of natural diamonds are identifiable by PL spectroscopy (Iakoubovskii and Adriaenssens, 2002;Titkov et al, 2008Titkov et al, , 2012Gaillou et al, 2010;Yuryeva et al, 2015). Our results from PL study of several yellow and pink diamonds are shown in Figure 14.…”
Section: Impurity Elements and Other Optical Defects (Ftir And Pl Data)mentioning
confidence: 83%
“…The 613 nm center is observed in diamonds of different types and has been described in many works [6,[34][35][36]. The ZPL at 612.4 nm was accompanied by phonon replicas with phonon energies of 17, 43 (longwave acoustic modes), and 77 meV (acoustic diamond lattice vibration) [6].…”
Section: Photoluminescencementioning
confidence: 83%
“…The ZPL at 612.4 nm was accompanied by phonon replicas with phonon energies of 17, 43 (longwave acoustic modes), and 77 meV (acoustic diamond lattice vibration) [6]. The PL lifetime equal to 10 −8 sec indicated an allowed transition [6]. The 613 nm center was noted to be more intensive in the cubic core than in the cubo-octahedral, peripheral zone of diamond crystals from the Mir deposit [9].…”
Section: Photoluminescencementioning
confidence: 96%
See 1 more Smart Citation